2021
DOI: 10.1177/07482337211037880
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia exacerbates cadmium-induced glomerular nephrosis

Abstract: Current research suggests that cadmium (Cd) exposure may be associated with the progression of diabetic nephropathy; however, the details of this relationship are insufficiently understood. The present study investigated the effects of elevated glucose on Cd-induced toxicity to glomerular cells using in vitro and in vivo models, and it demonstrated that Cd exposure and the hyperglycemia of diabetes acting together increased the risk of developing glomerular nephrosis . In vitro, human podocytes were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This variation could be due to differences in the frequency and dose of Cd exposure. This study, however, confirmed findings that exposure of hyperglycemic animals to Cd enhances the risk of renal injury [ 138 ]. Specifically, in vitro studies using cultured podocytes indicate that exposure to Cd under hyperglycemic conditions leads to mitochondrial dysfunction and ROS.…”
Section: Molecular Effects Of Environmental Toxicants On Ckd Progressionsupporting
confidence: 89%
See 2 more Smart Citations
“…This variation could be due to differences in the frequency and dose of Cd exposure. This study, however, confirmed findings that exposure of hyperglycemic animals to Cd enhances the risk of renal injury [ 138 ]. Specifically, in vitro studies using cultured podocytes indicate that exposure to Cd under hyperglycemic conditions leads to mitochondrial dysfunction and ROS.…”
Section: Molecular Effects Of Environmental Toxicants On Ckd Progressionsupporting
confidence: 89%
“…Interestingly, exposure of these mice to Cd also decreased serum leptin levels, which may enhance appetite and lead to weight gain. In contrast to these findings, a recent study using streptozotocin-induced diabetic mice (C57BL/6) exposed to Cd showed that body weight decreased after exposure [ 138 ]. This variation could be due to differences in the frequency and dose of Cd exposure.…”
Section: Molecular Effects Of Environmental Toxicants On Ckd Progressionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this study, we showed that leakage occurs to the extent that elevation of NAG does not occur, and there is the possibility that glomerular hyperfiltration and decrease of nephrons occur because of the decrease in plasma metabolites, creatinine and amino acids, and the broad elevation of urinary metabolites. Cd exposure has been suggested only for tubular disorders, but recent in vivo and in vitro studies have also focused on its effects on glomeruli at early, low concentrations exposure [ 63 , 64 ]. Thus, combined analysis of urinary and plasma metabolites could lead to better description of toxicological profiles of Cd in humans with deeper mechanistic understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The CCK-8 assay has been used to determine the proliferation of podocyte cells, including the MPC-5 cell line ( 46 ) and human podocytes ( 47 ). BrdU is a nucleoside analog of thymidine and its incorporation into DNA during replication within S-phase of the cell cycle is used to quantify cell proliferation ( 48 ).…”
Section: Discussionmentioning
confidence: 99%